О теоретическом и вероятностностатистическом подходах к определению оптимальной раскладки компьютерной клавиатуры - Гаджиев, А.Г.; Эфендиев, Г.Д. (Проблемы управления и информатики, 2009)
Розглядається теоретичний та ймовірнісно-статистичний підходи до визначення оптимальної розкладки комп’ютерної клавіатури. Запропоновано алгоритм, що дозволяє відшукати оптимальні варіанти розміщення букв різних алфавітів на комп’ютерній клавіатурі, за допомогою якого визначається оптимальна розкладка комп’ютерної клавіатури для азербайджанської мови. Theoretical and probability-statistical approaches to finding an optimal layout of a computer keyboard are considered. The algorithm allowing to find an optimal placement of various letters on a computer keyboard is suggested. This approach is based on the methods of probability theory, mathematical statistics and uses the specifiсity of the language. Applying this method to texts from different branches, an optimal placement of the letters of Azeri alphabet on a computer keyboard has been found.